The State of Food and Agriculture 1974 - Organisation des Nations Unies pour l'alimentation et l'agriculture (United Nations, 1974)
In addition to the usual review of the recent world food and agriculture situation, each issue of The State of Food and Agriculture from 1957 has included one or more special studies of problems of longer-term interest. This year’s edition focuses on the review of population, food supply and agricultural development by regions.